Role of viruses in febrile convulsions. - Lewis, H M (1979)
A disseminated viral illness was demonstrated by isolating a virus from the CSF, blood or urine in 27% of 73 children who were admitted to hospital after a first febrile convulsion. However, a viral aetiology could be implicated for 86% of the children after combining results of tissue culture, electron microscopy, mouse inoculation, complement fixation tests, and interferon assay. Parallel bacterial cultures showed a possible pathogen in 29% of children, but in only 4% was the pathogen isolated from the CSF, blood, or urine. No correlation was found between the nature of the pathogen (or evidence of its dissemination) and the severity of the convulsion, degree of fever, CSF protein, CSF white cells, or the WBC. The results suggest that a febrile convulsion could be a response to invasion of the blood stream or central nervous system by a micro-organism which is usually a virus. Invasion may be of such brief duration that successful isolation of the virus from the blood, CSF, or urine in not more commonly achieved.